A question of quality: the art/science of doing collaborative public ethnography. (August 2013) - Mosher, Heather
Social science researchers have long stressed the importance of a more publically relevant and accessible science. Nevertheless, significant barriers remain within the academy, such as processes for peer review, promotion, and awarding of degrees, which discourage the use of nontraditional dissemination techniques that support a more public ethnography. Concerns over scientific rigor, best practices, and methods for disseminating ethnographic research to public audiences may act as some of the barriers, among others. The purpose of this article is to discuss challenges in doing and disseminating collaborative ethnography to public audiences while still operating within the constraints of the academy. By sharing this experience, my intent is to stimulate debate and scholarship around assessing the quality of public ethnography using less traditional modes of reporting, such as video, and to encourage changes in peer review and institutional practices to more effectively support quality and dialogic dissemination of public ethnography that aims to bring together both academic and public audiences to address issues of great public significance.